Prevalence and associated factors of medical device-related pressure injuries in long-term care facilities: a multicenter cross-sectional study - Suzhen Zhang; Xiuying Zhuo; Mingming Zhang; Jianbing He; Qiuni Cai (Frontiers in Medicine, 2026)
Objective To determine the prevalence of medical device-related pressure injuries (MDRPIs) and identify their associated factors among residents in long-term care facilities. Methods A multicenter cross-sectional study was conducted between February and April 2025 across 11 long-term care facilities in Xiamen, China. A total of 380 residents were enrolled. MDRPIs were identified through systematic head-to-toe skin inspection and staged according to the National Pressure Injury Advisory Panel classification. Potential associated factors encompassing demographic characteristics, clinical status, device-related variables, and facility-level features were collected. Independent predictors were identified using multivariable logistic regression. Results The overall prevalence of MDRPI was 12.4% (47/380; 95% CI: 9.3%–16.1%). Among the 58 documented lesions, the most common sites were the nasal bridge (34.5%), ears (20.7%), and occiput (17.2%). Nasoenteric/nasogastric tubes accounted for 43.1% of injuries, and Stage 1 injuries were predominant (48.3%). Multivariable analysis identified four independent associated factors: edema (OR=3.49, 95% CI: 1.71–7.13, p < 0.001), anemia (OR=2.41, 95% CI: 1.23–4.72, p = 0.010), use of two devices (OR=2.48, 95% CI: 1.10–5.59, p = 0.028) and three or more devices (OR=5.10, 95% CI: 2.20–11.82, p < 0.001) compared with one device, and poorer nutritional status (per 1-point decrease in Mini Nutritional Assessment-Short Form score; OR=1.33, 95% CI: 1.10–1.60, p = 0.003). Conclusions Approximately one in eight long-term care residents had MDRPIs. Edema, anemia, multiple device use, and poor nutritional status were significant modifiable associated factors. Routine assessment of these factors and targeted prevention strategies are warranted to reduce the burden of device-related injuries in long-term care settings.